The nutritional needs of moderate–late preterm infants. (2nd April 2022) - Johnson, Mark J; King, Caroline; Boddy, Bethany; Craig, Stan; Males, Joanna; McEwan, Tom; Tagani, Stephanie
Abstract : This article discusses the nutritional needs of moderate and late preterm infants (born between 32+0weeks and 36+6weeks' gestation) and makes recommendations for best practice both while these infants are in hospital and when they are discharged into the community. These recommendations were derived following a roundtable meeting of a group comprising two neonatologists, three paediatric dietitians, a health visitor/paediatric nurse and a midwife practitioner. The meeting and medical writing assistance was sponsored by Nutricia. None of the participants accepted honoraria for their contributions to the discussion.